RANCANG BANGUN SISTEM KEAMANAN JARINGAN MIKROTIK MENGGUNAKAN FIREWALL FILTERING DAN PORT KNOCKING DENGAN NOTIFIKASI TELEGRAM PADA EVENT VIRTUAL - Febri, Febri; Hutabri, Ellbert (LPPM Universitas Putera Batam, 2023)
Network security is a very important aspect in maintaining information security. In network management using proxy devices, use of firewall filtering and port knocking in an effort to increase security and control network access and hide services that are not needed. In addition to obtaining information on suspicious network activity in real-time with telegram notifications. The method used includes analysis of network security needs, system architecture design, firewall filtering and port knocking configurations on the proxy and integration with the telegram API to send notifications. The results of this study show that using firewall filtering and port knocking on Mikrotik can effectively improve network security by limiting unauthorized access and reducing the risk of attacks from outside. The system is also capable of providing notifications via telegram when suspicious activity is detected, thus enabling a network administrator to respond quickly to these threats